2008
DOI: 10.1177/1049732308321755
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Issues in Emergent Evaluations of Health Programs: Lessons From Iberoamerica

Abstract: There has been growing interest in nonmainstream approaches to assessing health programs, but methodological strategies have not been a concern. In this article, we review methodological strategies used in emergent evaluations of health policies and programs in Iberoamerica, focusing on participatory, qualitative, critical, hermeneutical, bottom-up, collaborative, and transdisciplinary approaches. A literature search was performed combining strategies: database review, consultation of bibliography, expert inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…This approach applies principles of transparency, collaboration, participation, and democracy with key stakeholders who are engaged as co-researchers within the design, implementation and analysis data in of the inquiry process (Mercado-Martinez, Tejada-Tayabas, & Springett,, 2008). Emergent approaches draw on both quantitative and qualitative methods to evaluate aspects of a program that are relevant to the various stakeholders (Mercado-Martinez et al).…”
Section: Research Methodology: Participatory Action Research and Evalmentioning
confidence: 99%
“…This approach applies principles of transparency, collaboration, participation, and democracy with key stakeholders who are engaged as co-researchers within the design, implementation and analysis data in of the inquiry process (Mercado-Martinez, Tejada-Tayabas, & Springett,, 2008). Emergent approaches draw on both quantitative and qualitative methods to evaluate aspects of a program that are relevant to the various stakeholders (Mercado-Martinez et al).…”
Section: Research Methodology: Participatory Action Research and Evalmentioning
confidence: 99%
“…All three ACCOs identified that their programs were not being evaluated and reported in ways that reflect how they address social determinants of First Peoples’ health and the holistic nature of their design [5]. This is not unique to this region or country [6–8]. Each of the ACCOs were locked into certain funding arrangements (which largely neglected prevention activities) that prevented them working together to achieve common goals.…”
Section: Introductionmentioning
confidence: 99%
“…Among other goals, these methods seek to improve the management of public programs by promoting the democratization of institutions, by strengthening the transparency of the processes involved and empowering the programs’ beneficiaries to take a more active role, and by promoting the participation of individuals or groups traditionally excluded (Mercado, Tejada-Tayabas, & Springett, 2008). …”
Section: Introductionmentioning
confidence: 99%